(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2019)
Business operation in Corporate Social Responsibility (CSR) approach supports competitiveness and sustainable development. In Hungary the approaches of social responsibility and sustainability started to develop after the change of regime, mainly through international corporate cooperation. However, in our days not only companies are expected to operate in a sustainable and responsible way, but it is indispensable that the demand and aspirations in this direction should be reflected in society as well, since besides processes applied in production, it is the consumption that can contribute most to the realization of sustainability. The purpose of this study is to examine whether consumers know the CSR activity of the shop they visit, as well as to highlight the aspects influencing their choice. Furthermore, the study also reveals the socially responsible activities that would be supported by them. The customers of an international food chain company – is a leader in CSR activities - were involved in the questionnaire survey. This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.